A de novo substitution in BCL11B leads to loss of interaction with transcriptional complexes and craniosynostosis. (3rd April 2019) - Goos, Jacqueline A C; Vogel, Walter K; Mlcochova, Hana; Millard, Christopher J; Esfandiari, Elahe; Selman, Wisam H; Calpena, Eduardo; Koelling, Nils; Carpenter, Evan L; Swagemakers, Sigrid M A; van der Spek, Peter J; Filtz, Theresa M; et al.
Abstract: Craniosynostosis, the premature ossification of cranial sutures, is a developmental disorder of the skull vault, occurring in approximately 1 in 2250 births. The causes are heterogeneous, with a monogenic basis identified in 25% of patients. Using whole-genome sequencing, we identified a novel, de novo variant in BCL11B, c.7C>A, encoding an R3S substitution (p.R3S), in a male patient with coronal suture synostosis. BCL11B is a transcription factor that interacts directly with the nucleosome remodelling and deacetylation complex (NuRD) and polycomb-related complex 2 (PRC2) through the invariant proteins RBBP4 and RBBP7. The p.R3S substitution occurs within a conserved amino-terminal motif (RRKQxxP) of BCL11B and reduces interaction with both transcriptional complexes. Equilibrium binding studies and molecular dynamics simulations show that the p.R3S substitution disrupts ionic coordination between BCL11B and the RBBP4–MTA1 complex, a subassembly of the NuRD complex, and increases the conformational flexibility of Arg-4, Lys-5 and Gln-6 of BCL11B. These alterations collectively reduce the affinity of BCL11B p.R3S for the RBBP4–MTA1 complex by nearly an order of magnitude. We generated a mouse model of the BCL11B p.R3S substitution using a CRISPR-Cas9-based approach, and we report herein that these mice exhibit craniosynostosis of the coronal suture, as well as other cranial sutures. This finding provides strong evidence that the BCL11B p.R3S substitution is causally associated with craniosynostosis and confirms an important role for BCL11B in the maintenance of cranial suture patency.